MULTI LEVEL MARKETING (MLM) CNI DALAM PERSPEKTIF HUKUM ISLÂM - Abd. Wahed (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2008)
The current development of business affair demands the Muslim thinkers to purpose a respond about how it should be from the view of Islamic economy. Commercial business with the leveling method which is known as Multi Level Marketing (MLM) like CNI appears elements of bay’, an Islamic economic system of buy and sell. However, a further study , using Islamic law establishment method, proves that there are obvious distinctions between the system of multi level marketing and Islamic economic system. This effects the differentiation of both systems in the perspective of Islamic law. Through the method of al-mashlahah , it is proved that Multi Level Marketing is greater in terms of its mafsadah than its usefulness. This argument leads to a conclusion that multi level marketing is considered illegal or haram.